1997
DOI: 10.1182/blood.v89.1.26.26_26_31
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Activity in Reactive and Neoplastic Lymphoid Tissues: Infrequent Detection of Activity in Hodgkin's Disease

Abstract: We used the recently described sensitive and rapid detection assay called telomeric repeat amplification protocol (TRAP) to detect telomerase activity in lymphoblastoid (n = 5) and lymphoma cell lines (n = 7), hyperplastic lymph nodes (n = 6) and tonsils (n = 5), and tissues involved by non-Hodgkin's lymphoma (NHL) (n = 43) and Hodgkin's disease (HD) (n = 14). Clearly evident telomerase activity was found in all lymphoblastoid and lymphoma cell lines, and in 34 of 43 cases (80%) of NHL. These results were expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…To our knowledge, this is the first large study of telomerase activity in various types of B‐NHLs. The results confirm the findings of previous smaller studies that showed telomerase activity to be present in vivo in most types of B‐cell lymphoma 7, 11, 13, 15, 16, 19. However, we found that low grade MZBCLs of extranodal, nodal, and splenic types lacked telomerase activity or had an extremely low level of telomerase.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…To our knowledge, this is the first large study of telomerase activity in various types of B‐NHLs. The results confirm the findings of previous smaller studies that showed telomerase activity to be present in vivo in most types of B‐cell lymphoma 7, 11, 13, 15, 16, 19. However, we found that low grade MZBCLs of extranodal, nodal, and splenic types lacked telomerase activity or had an extremely low level of telomerase.…”
Section: Discussionsupporting
confidence: 91%
“…Data regarding telomerase levels in MZBCLs are scarce in previously published studies. One study found an unquantified amount of telomerase in a single case of “monocytoid lymphoma” of an unspecified type and in one of two cases of “villous lymphocytic lymphoma” 11. In our study, the absence of telomerase activity was found to be unique to low grade marginal zone lymphomas.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Human palatine tonsil was found to express telomerase activity that was as high as that in lymphoma. 19,20) This strong telomerase activity seemed to be derived from normal germinal centers, which were also commonly found in activated nasopharyngeal lymphoid tissues. It is thus reasonable that non-malignant nasopharyngeal tissue presenting an inflammatory focus, as well as many activated lymphoid cells, also expresses telomerase activity.…”
Section: Discussionmentioning
confidence: 99%